Beauty Is in the Eye of the Beholder: Esthetic Outcome Assessment in Smile Reanimation Surgery in Patients With Facial Palsy. Issue 1 (January 2021) - van Veen, Martinus M.; Broekstra, Dieuwke C.; Mureau, Marc A.M.; Werker, Paul M.N.; Dijkstra, Pieter U.
Abstract : Abstract: Layperson assessments are becoming increasingly important in the evaluation of surgical procedures of the face, including smile reanimation. In this study, the authors set out to answer 3 questions: (1) are esthetic scores more dependent on the assessor or the person that is being assessed, (2) how does smile reanimation change esthetic scores, (3) do sex and age of the patient and assessor explain some of the esthetic outcomes? Thirty-five assessors scored pre and postoperative photographs of 21 facial palsy patients undergoing smile reanimation. Linear mixed-effect models were used to investigate the effects of assessor and patient factors on esthetic outcome assessments, to examine changes after smile reanimation, and to determine whether sex and age explained part of the esthetic outcomes. Fifty-eight percent of variation in the esthetic scores can be explained by some assessors being more positive in their esthetic scoring compared to other assessors. Twenty-nine percent was attributed to patient baseline esthetic scores. Overall esthetic scores improved after smile reanimation. Sex and age of the patient and assessor could not explain variation in the esthetic scores. Esthetic appearance highly depends on "who is looking." These findings are important for preoperative counseling, and for those treating and educating patients with facial palsy. Abstract : Supplemental Digital Content is available in the text